1988
DOI: 10.1002/ajpa.1330770306
|View full text |Cite
|
Sign up to set email alerts
|

Founder effect and genetic disease in Sottunga, Finland

Abstract: Pedigree data are analyzed in order to determine the factors responsible for the high frequencies of certain genetic disorders in an isolated Swedish-speaking population of Finland's A land archipelago. The founders of Sottunga are identified, and the genetic contributions of each founder to descending birth cohorts are estimated. Founders born before 1700 have far more descendants in the contemporary gene pool than do more recent founders. However, because of migration and depopulation since 1900, the expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…However, some of these Baltic islands have experienced considerable sea traffic and may have been less isolated than previously thought [64]. Indeed, the disease haplotype diversity is consistent with genealogical studies that have shown it is extremely unlikely that one or very few founders introduced von Willebrand disease mutations into this population [65, 66]. Because of allelic heterogeneity at the VWF locus, no disequilibrium is observed between the disease phenotype and these polymorphisms [29].…”
Section: Discussionsupporting
confidence: 55%
“…However, some of these Baltic islands have experienced considerable sea traffic and may have been less isolated than previously thought [64]. Indeed, the disease haplotype diversity is consistent with genealogical studies that have shown it is extremely unlikely that one or very few founders introduced von Willebrand disease mutations into this population [65, 66]. Because of allelic heterogeneity at the VWF locus, no disequilibrium is observed between the disease phenotype and these polymorphisms [29].…”
Section: Discussionsupporting
confidence: 55%
“…Instead, in mainland Finland founder effect and genetic drift originally operating within geographical isolates have been identified as significant factors in the distribution patterns and prevalence of some 36 disease genes, collectively described as the Finnish Disease heritage (Norio, 2003), with random inbreeding due to probably unrecognized remote consanguineous marriages making only a limited contribution to disease gene expression (Papponen et al 1999;Peltonen et al 1999;Norio, 2003). In the studies on theÅland Islands, small effective population size and drift were cited as the primary factors behind the high frequency of recessive disorders (O'Brien et al 1988a(O'Brien et al , 1988b.…”
Section: Discussionmentioning
confidence: 99%
“…The northern part of the country was colonized later by Finnish migrants from the south, with little input from abroad. Several founding events took place, subsequently leading to regional homogeneities and a specific pattern of inherited disorders within the Finnish population (Peltonen et al 1995;Kittles et al 1999;O'Brien et al 1988).…”
Section: The Genetic Profile Of the Quebec Populationmentioning
confidence: 99%
“…where S is the sample of subjects linked to the founder, P is the number of genealogical paths between a founder and each subject and g is the number of generations in each path connecting the founder and the subject (Roberts 1968;O'Brien et al 1988;Heyer and Tremblay 1995). Dividing this result by the number of subjects gives the proportion of the subjects' gene pool that comes from that founder.…”
Section: Demogenetic Analysesmentioning
confidence: 99%